MOOCs Innovation for MICE Education: Strengthening Digital and Sustainable Competence in Tourism Learning - Khairunnisa Khairunnisa; Rezki Orientani; Yulita Suryantari (Jurnal Teknologi Informasi dan Pendidikan, 2026)
The tourism industry is undergoing rapid transformation driven by digitalization, sustainability imperatives, and evolving learner expectations. Within this context, the MICE sector requires professionals who are digitally competent and sustainability-oriented. Traditional classroom approaches often fail to keep pace with these demands, while Massive Open Online Courses (MOOCs) offer scalable and flexible alternatives. This study investigates the role of MOOCs innovation in enhancing digital literacy and sustainability education in MICE learning. Drawing on Constructivist Learning Theory and Competency-Based Education, a quantitative survey was conducted with 42 undergraduate students who had completed a MICE course at Universitas Terbuka, Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The measurement model demonstrated strong reliability and validity, and the structural model showed moderate to substantial explanatory power. Results confirmed that MOOCs innovation significantly influences both digital literacy and sustainability education, with digital literacy emerging as the strongest predictor and a key mediator between innovation and sustainability outcomes. These findings extend theoretical understanding by demonstrating how MOOCs innovation operationalizes constructivist and competency-based approaches in specialized tourism education. Practically, the results emphasize the importance for educators, curriculum designers, and policymakers to prioritize digital literacy as the most effective pathway toward sustainability-oriented learning outcomes. The study concludes that MOOCs innovation offers a strategic tool for preparing future-ready MICE professionals equipped with digital and sustainability competencies.